ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED TERHADAP RETURN SAHAM - Kartini Kartini; Gatot Hermawan (University of Merdeka Malang, 2008)
This research purposes were to prove the hypothesis consisted of: (1) EVA which hada positive correlation to the stock return, (2) MVA which had a positive correlation to the stockreturn. This research used regression analysis to find how much the contribution of theindependent variable in influencing the stock return was. Data used in this research was asecondary data provided by Jakarta Stock Exchange (JSX) since 2005 until 2006. The type ofdata analyze was manufacturing companies sub consumers goods, from 2005 to 2006. Theconclusion of this research was that EVA and MVA did not significantly influence the stockreturn. This was proved by the evidence of the Fstatistic which was lower than the Ftable(1,0753,15) and the significance was more than 0.05 (r0.05). EVA did not positively correlateto the stock return. It was proved by the significances of 0,695 higher than 0.05 (p0,05). MVAdid not positively correlate to the stock return. It was proved by the significances of 0,238higher than 0.05 (p0,05).